Constraints Faced by Livestock’s Farmer in Adoption of Scientific Technology - Meena, K. L.; Meena, H. R.; Chauhan, T. R.; Kumar, Manoj; Chowdhury, P. (Indian Journal of Hill Farming, 2018)
The study was conducted to review the situation of animal husbandry in Rohilkhand region of Uttar Pradesh with the objective to identify major constraints of the livestock farmers in adapting the recommended animal husbandry practices. The respondents were undergone training at the KVK, IVRI in various aspects of animal husbandry. The study revealed that limited space and other resources available for providing scientific housing to dairy animals was the very serious constraints as experiences by the respondents. The second rank constraint was non-availability of livestock extension officers and veterinary doctors in time among respondents; Preference for natural service is the third serious constraints in adoption of improved dairy farming practices. Respondents reported that there was no dearth of scrub bulls, but lacking good quality bulls. Many time farmers preferred these scrub bulls because of distant availability of good quality bulls. Other reasons for prefer natural servicing is the lack of A.I. centre, distant location of veterinary dispensary, lack of awareness about A.I. and improved breeding practices. Prevalence of the belief that colostrums feeding is unhygienic and it may be harmful to the health of newborn calves.